Locusts as a sustainable protein source: perceptions and nutritional awareness among Saudi citizens - Alhajri, Ahlam Saleh (Frontiers in Sustainable Food Systems, 2025)
BackgroundLocusts are traditionally consumed in Saudi Arabia and recognized globally for their high nutritional value and environmental sustainability. However, their acceptance as a mainstream protein source remains limited due to psychological and cultural barriers.AimThis study aimed to assess locust consumption patterns, nutritional awareness, and public acceptance among Saudi citizens, with implications for sustainable nutrition and food security.MethodsA cross-sectional survey was conducted with 564 participants using a structured questionnaire. Data were analyzed using descriptive statistics, ANOVA, and Pearson correlation.ResultsOnly 24.1% had ever consumed locusts. Nutritional awareness was high, with 72.3% identifying locusts as protein rich. Half (50.0%) considered them a sustainable protein alternative. Willingness to try processed locust products was 37.2%. ANOVA revealed no significant demographic differences (p > 0.05), and the correlation between sustainability perception and willingness was weak (r = −0.0246).ConclusionAlthough awareness is growing, public acceptance remains modest, highlighting the need for education and culturally appropriate interventions to promote edible insect consumption.